CONTINUITY IN THE PROFESSIONAL PREPARATION SYSTEM OF SOCIAL PEDAGOGES - Kornjat, Vira (Educological discourse, 2018)
The article deals with the problem of professional preparation of specialists is given in the article, in particular her continuity. Understanding is analysed scientists essence of concepts «professional education», «professional preparation». Professional education is understood as the totality of knowledge, skills and ability, the acquisition of which allows you to work as a specialist of higher and advanced qualifications; training in specialized educational institutions for the three-year activity in the national branch of the national economy, nauki, cultury; flashing chest system of education. It is shown that the main component of vocational education is vocational training; gives the people the opportunity to receive a certain professional quali fi cation that will determine her place in the society. The main factors in the process of professional training are the formation of an educated and solid personality, a healthy learning experience in life, a reformation of the professional education and a higher education, and the formation of a willingness to self-education. The main factors in the process of professional training are the formation of an educated and solid personality, a healthy learning experience in life, a reformation of the professional education and a higher education, and the formation of a willingness to self-education. The professional training of social educators is understood as a process that perpetuates the discipline of the professional personality orientation, the assimilation of the negligence of theoretical knowledge, the formation of practical skills and skills, the accumulation of experience, the result of which is the willingness to exploit socio-pedagogical activity. Professional training of social pedagogues is carried out in colleges, institutes, universities, at such educational levels as junior specialist, bachelor, master. The first link in the profession is a pedagogical college. The organization of the educational process has its peculiarities, in particular the following: possibility of obtaining general secondary education and vocational training; taking into account age characteristics of students in organizing the educational process, especially at the first and second courses; orientation of programs for further deepening of knowledge and skills during studying at the institute, university; practical orientation of education, which is expressed in different types of pedagogical practice, the number of their hours; Extended responsibilities and responsibilities of curators of student groups.